Femtosecond switching of strong light-matter interactions in microcavities with two-dimensional semiconductors - Armando Genco; Charalambos Louca; Cristina Cruciano; Kok Wee Song; Chiara Trovatello; Giuseppe Di Blasio; Giacomo Sansone; Sam A. Randerson; Peter Claronino; Kyriacos Georgiou; Rahul Jayaprakash; Kenji Watanabe; et al. (Nature Communications)
Abstract Ultrafast all-optical logic devices based on nonlinear light-matter interactions hold the promise to overcome the speed limitations of conventional electronic devices. Strong coupling of excitons and photons inside an optical resonator enhances such interactions and generates new polariton states which give access to unique nonlinear phenomena, such as Bose-Einstein condensation, used for all-optical ultrafast polariton transistors. However, to reach the threshold for condensation high quality factors and high pulse energies are required. Here we demonstrate all-optical switching exploiting the ultrafast transition from the strong to the weak coupling regime in low-Q microcavities embedding bilayers of transition metal dichalcogenides with high optical nonlinearities and fast exciton relaxation times. We observe a collapse of polariton gaps as large as 55 meV, and their revival, lowering the threshold for optical switching below 4 pJ per pulse, while retaining ultrahigh switching frequencies. As an additional degree of freedom, the switching can be triggered pumping either the intra- or the interlayer excitons of the bilayers at different wavelengths, speeding up the polariton dynamics, owing to unique interspecies excitonic interactions. Our approach will enable the development of compact ultrafast all-optical logical circuits and neural networks, showcasing a new platform for polaritonic information processing based on manipulating the light-matter coupling.